Statistical assessment of EV usage potential from user's perspective considering rapid-charging technology. (October 2018) - Krause, Julia; Ladwig, Stefan; Schwalm, Maximilian
Highlights: Electrical vehicle usage potential highly depends on trip purpose Rapid-charging (RC) technology can increase the perceived usage potential of a BEV. The perceived additional value of RC technology depends on trip purpose. More leisure trips are manageable with RC options at optimal position en route. No differences between BEV users and nonusers in perceived usefulness of RC options. Abstract: The aim of the German Government is the licensing of one million electric vehicles (EV) in Germany until 2020. However, the number of battery electric vehicles (EVs) today still is just above 25, 000. There are several reasons for deciding against an EV, but especially low battery ranges as well as too long perceived charging duration inhibit the usage of an EV. To eliminate the negative influence of these two reasons on the decision to purchase an EV, a novel charging technology is established. The rapid-charging technology enables the user to recharge the battery to 80% of its state of charge (SOC) within 20–30 min. For the examination of the technology's impact from (potential) user's perspective, users and nonusers of battery electric vehicles were questioned about the perceived additional value of public rapid-charging infrastructure by taking into account different trip purposes and running comparisons to regular charging options. The results show an increased perceived value especially for trips with leisure purpose, considering their share of all trip purposes in Germany, according to the MiD 2008. In order to increase the number of licensed EVs in Germany, the study's results also suggest further dissemination of information on rapid charging which might influence the perceived usefulness of the technology and consequentially the perceived usefulness of an EV.